Similarities and differences between gouty arthritis and rheumatoid arthritis—an interesting case with a short look into the literature - David Kiefer; Judith Erkenberg; Juergen Braun (Exploration of Musculoskeletal Diseases)
Gout often presents as acute arthritis but may also present with chronic joint inflammation. For the diagnosis of an acute gout attack with its typical symptoms, the differentiation towards a bacterial joint infection is critical and mandatory. The detection of intracellular uric acid crystals in the synovial fluid of affected joints is important for the initial diagnosis of gout. In the case of a chronic course with polyarticular joint involvement, the differentiation from other inflammatory rheumatic diseases such as rheumatoid arthritis (RA) can be challenging. The case presented here is of interest because the patient initially had characteristic clinical symptoms of tophaceous gout including a typical medical history—even though rheumatoid factor and anti-citrullinated protein antibodies (anti-CCP) were positive. The course of the disease and the critical evaluation of all findings also, and most interestingly, including histological results finally suggested a main diagnosis of RA.